Staroruskie Słowo o mądrości przypisywane Cyrylowi z Turowa (edycja i przekład) - Brzozowska, Zofia (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
The Word of Wisdom is a relatively small-sized relic of medieval eastern Slavic literature from what is certainly the oldest period of its existence, i.e. from before the Mongol invasion of Rus. It is attributed usually to Cyril of Turov (who died before 1182), one of the greatest writers of the Old Russian period. The oldest manuscript containing the full text of the Word of Wisdom is the parchment code from the thirteenth century, which is currently stored in the collections of the National Library of Russia in Saint Petersburg. A small fragment of the Word of Wisdom was also written on a birch bark document, found in its entirety in Torzhok near Novgorod the Great. This relic is usually dated to the years 1170-1190.